Spent Fuel Leaching in the Presence of Corroding Iron. (5th January 2017) - Puranen, Anders; Barreiro, Alexandre; Evins, Lena Z.; Spahiu, Kastriot
ABSTRACT: The Swedish spent nuclear fuel canister design KBS-3 consists of a cylindrical copper shell surrounding an iron insert that holds the spent fuel. Like in most other canister designs the mass of iron constitutes the majority of the canister weight. In order for groundwater to access the spent fuel in a future repository the copper shell must fail and iron corrosion occur. Spent nuclear fuel dissolution will therefor likely proceed under conditions of simultaneous anoxic iron corrosion. The iron corrosion can likely suppress the spent fuel release by creation of strongly reducing conditions from Fe(II) formation and the generation of large quantities of hydrogen. Redox sensitive radionuclides may either be reductively precipitated by dissolved Fe(II) or from interaction with iron corrosion products such a magnetite or green rusts. The generated hydrogen (up to several MPa) may also inhibit the spent nuclear fuel dissolution at the surface of the fuel via the so called hydrogen effect. In order to probe these effects an autoclave experiment was performed in which a basket with PWR spent nuclear fuel (burnup ∼43 MWd/kgU) was suspended in an autoclave containing a simplified groundwater (10 mM NaCl, 2 mM NaHCO3 ) with iron powder. The autoclave was sparged and pressurized with argon. Following an initial rise in radionuclide concentrations from dissolution of pre-oxidised phases the U concentration dropped to 3x10 -9 M within 76 days, in-line with the solubility of amorphous UO2, expected to form under reducing conditions. Any Cs and Sr release also ceased within 223 days indicating complete transition from dissolution of pre-oxidized phases and instant release fractions to conditions with inhibition of the dissolution of the fuel matrix. Gas phase analysis and pressure monitoring showed a steady build-up of hydrogen at a rate higher than what could be attributed to radiolysis, reaching hydrogen partial pressures of several hundred kPa. The results indicate continuous corrosion of iron, with magnetite as the dominating iron corrosion product.